Proceso de atención de enfermería en paciente masculino de 25 años con sars-cov-2. - Duarte Jaña, Karen Nathaly (2020)
Sars cov-2 is a disease of recent description of viral cause, with a nonspecific clinical picture, its main symptoms are headache, fever, and myalgia, within its main complication in adults we have pulmonary involvement causing pneumonia, which causes respiratory distress, which can lead to the use of mechanical ventilation. In the following case we report a 25-year-old patient with Sars cov-2, in which the medical evaluation and the nursing intervention were performed. This disease has an incubation time that ranges from 4 to 7 days, before presenting clinical symptoms, as it is a pathology that attacks the respiratory tree, it is spread by microdroplets of flush from infected people. Although there is no specific treatment, what we are trying to do as a health team is to control the symptoms and educate the user, seeking the complete replacement of their vital functions.